NHL-2007 familial predisposition for non-Hodgkin lymphomas in childhood and adolescence - Schulz, Solveig Christine; Justus Liebig University Giessen (My University, 2015)
In Germany, NHL are the third most common cancer in children. Although significant progress has been made in the treatment of childhood NHL, the majority of etiological factors of NHL and its subtypes remain unclear. The NHL-2007 study aimed to determine if there is an excess of malignancies, especially lymphoid malignancies in relatives of childhood NHL patients for the entire group, as well as for distinct biological subgroups of childhood NHL.In the NHL-2007 study included participants were former patients with NHL in childhood (ages 0-15) who were treated in cooperative, multicenter study groups between 1986 and 2007 in Germany.

Non-Hodgkin-Lymphome (NHL) sind in Deutschland die dritthäufigste maligne Erkrankung im Kindesalter. Während die Medizin einen bedeutenden Fortschritt bei der Behandlung von NHL im Kindesalter verzeichnet, sind nur wenig Forschungsergebnisse mit Bezug auf die Ätiologie des NHL und seinen Subtypen bekannt. In die NHL-2007 Studie wurden alle (ehemaligen) Patienten eingeschlossen, die an NHL im Kindesalter erkrankt waren (Altersspanne 0-15) und in den multizentrischen Behandlungsstudien von 1986 bis 2007 in Deutschland behandelt worden sind.Für die NHL-2007 Studie wurde ein eigens angefertigter Fragebogen entwickelt und in einer Pilotstudie getestet. Entsprechend der Ergebnisse der Pilotstudie wurde der Fragebogen für die NHL-2007 Studie optimiert und eine passende Datenbank programmiert.
NHL-2007 - familiäre Prädisposition für Non-Hodgkin-Lymphome bei Kindern und Jugendlichen
Keywords: ddc:610